P15 Regional cerebral atrophy and cognitive function in Chronic Obstructive Pulmonary Disease. (12th November 2015) - Savage, CC; Pennington, C; Jones, PW; Dodd, JW
Abstract : Background: Widespread white matter damage and cognitive impairment have been demonstrated in COPD. However, it remains unclear if regional atrophy is present. We used a simple clinical visual rating scale to measure regional atrophy in a well-characterised population with COPD and compared age-matched controls. We explored correlations with demographics, disease factors and cognitive measures. Objectives: a) To determine if there are significant differences in regional atrophy between COPD patients and age-matched control subjects. b) To investigate whether patient characteristics or measures of disease severity account for group differences in atrophy severity. c) To seek correlations with regional atrophy. Methods: A validated visual analogue MRI grading technique was used to assess the degree of atrophy in multiple brain regions in stable non-hypoxaemic COPD patients (n = 25) and age-matched control subjects (n = 25). This study is a further analysis of a previous case-control multi modal cranial MRI study. 1 Main results: COPD patients had significantly greater frontal atrophy than control subjects (p = 0.01), this was independent of smoking history, comorbidities and hospital anxiety and depression scores. Cognitive function was significantly worse in the COPD group for executive function, working memory, verbal memory and processing speed. Group differences in atrophy did not seem to account for differences in cognitive function. We were unable to identify meaningful correlations between regional atrophy and disease severity or cognitive function. Conclusions: There is significant frontal brain atrophy in stable non-hypoxaemic COPD patients. This regional atrophy does not appear to be related to disease severity or cognitive function. Further work is needed to identify causative mechanisms behind this structural change. Reference: 1 Dodd JW, Chung AW, van den Broek MD, Barrick TR, Charlton RA, Jones PW. Brain structure and function in chronic obstructive pulmonary disease: a multimodal cranial magnetic resonance imaging study. Am J Respir Crit Care Med . 2012;186 :240–245